Hand Hygiene and Hand Sanitizers - Amy Simonne (EDIS, 2019)
Hand hygiene is one of the primary methods used to reduce the fecal-oral transmission of infectious agents. However, conflicting hand hygiene recommendations for different settings are causing confusion among the general public as to what is the best practice to follow or what products should be used for daily handwashing and hand hygiene. This document provides the information necessary for average consumers to make an informed decision.